Voluntarily chosen roles and conscientious objection in health care - Robinson, Michael (Journal of medical ethics, 2022)
The longstanding dominant view is that health care practitioners should be permitted to refrain from participating in medical interventions when they have a conscientious objection to doing so in a broad range of cases. In recent years, a growing minority have been fervently advocating a sea change. In their view, medical professionals should not be permitted to refuse to participate in medical interventions merely because doing so conflicts with their own moral or religious views. One of the most commonly offered arguments in support of this position focuses on the fact that health care practitioners knew what they were getting into when they voluntarily chose to take on their professional roles; nobody forced them to do this. I will argue that, despite its popularity among opponents of conscientious refusal, this argument from voluntariness fails to provide us with a good reason to reject broad accommodationism in favour of non-accommodationism.